To Assess the Impact of Oral Quality of Life (QoL) in Teenage Population with Habit History of Tobacco/Areca Nut/Gutka/Smoking Using OHIP-14 in Bhilai Region - Swati Prasad; Alok Avinash; M. C. Shashikanth; Umesh C. Chaudhary (Journal of Indian Academy of Oral Medicine and Radiology)
Aim: To assess the impact of Oral Quality of Life (QoL) in teenage population with habit history of tobacco/ areca nut/ gutka/ smoking using OHIP-14 in Bhilai region. Methodology: The present study was conducted in the Department of Oral Medicine and Radiology, Rungta College of Dental Sciences and Research, Bhilai, Chhattisgarh. 500 subjects were divided into two groups: Group I: comprise of 250 subjects with any deleterious habits of tobacco, gutka, areca nut, cigarette etc. (study) and Group II: comprise of 250 subjects without any deleterious habit as (control). All the subjects were explained about the questions and were asked to fill up their responses in the questionnaire using OHIP-14. Results: Mean scores of two different domains of OHIP-14, including Physical Pain (4.82 ± 2.85) and Physical Disability (4.04 ± 2.45) was found to be more in study group when compared to control (0.57 ± 0.98 & 0.34 ± 0.63). Subjects with the smokeless form of tobacco consumption and both form (smoking and smokeless) had significantly higher mean in domain of Physical pain as compared to those who had the habit of only smoking. The mean score of sum of OHIP-14 was found to be significantly worse in the study group as compared to controls. Conclusion: The results suggest that the concept of OHRQL is important in clinical practice of dentistry and dental education as well. People are more likely to be motivated and behave positively when they understand how habits related oral mucosal diseases affect their QoL.